Cervical length of preoperative cervical cerclage prognostic impacted the effect of cervical insufficiency - Yayun Zhang; Zihan Zhao; Jiaqi Xu; Fei Wu; Ting Chen; Shunyu Hou; Aifen Wang (BMC Pregnancy and Childbirth)
Abstract Background This study aimed to analyze the impact of preoperative cervical length before cervical cerclage on the extension of gestational days in patients with various diagnostic types of cervical insufficiency, including obstetric history-based diagnosis, ultrasound-based diagnosis, and physical examination-based diagnosis. Methods 168 patients were segregated into four categories based on cervical length: 0–0.4 cm, 0.5–1.4 cm, 1.5–2.4 cm, and ≥ 2.5 cm. Kaplan-Meier, linear regression curve and Cox regression analyses were used, with a focus on clinical variables, particularly cervical length and the duration of extension after cervical cerclage. Results The length of the cervix prior to cervical cerclage correlated with the prognosis of 168 postoperative patients by linear regression analysis. When delivery beyond 28 or 34 weeks was set as the primary prognostic indicator, univariate Cox analysis showed that postoperative C-reactive protein (CRP) level was identified as a risk factor for gestational age extension in cervical cerclage patients. Longer cervical length was identified as a protective factor for overall gestational age extension in cervical cerclage patients. In addition, the obstetrical-history diagnosis group had a better prognosis compared to the emergency cerclage group, which had a worse prognosis compared to the ultrasound-based diagnosis group. Kaplan-Meier curve analysis of all patients revealed a statistically significant impact of different cervical lengths on the gestational age of delivery (P < 0.001). However, in the physical examination-based diagnosis group, Kaplan-Meier curve analysis demonstrated a statistically significant impact of different cervical lengths on gestational age at delivery (P = 0.006). Conclusion Longer preoperative cervical length was associated with better outcomes in terms of gestational prolongation and newborn survival after cervical cerclage.